Deposition and characterization of carbon thin films by varying substrate bias and temperature - Chow, Wai Leong. (2010)
The carbon film composition in terms of sp2 or sp3 can differs by varying different deposition techniques and/or parameters. In this project, Filtered Cathodic Vacuum Arc (FCVA) deposition technique is used while in-situ substrate bias and temperature are being varied. For substrate bias, there may be two completing factors associated to it. One is solely the substrate bias itself which affects the ion energy. Another is substrate heating effect which comes into play when the applied bias is high enough to generate sufficient thermal energy to heat up the substrate. Hence it is important to verify and understand the impact of substrate heating on the properties of carbon film. Results here have shown that substrate heating effect occurs at high bias of -300V. For substrate temperature, it is known that there is a phase change from a low sp2 to high sp2 carbon film when being subjected to high temperature. Carbon atoms gain enough energy to relieve stress and this creates alignment in a preferred orientation. This form of carbon film is known as Vertically Orientated Carbon (VOC). Thus it is important to identify the temperature that is required for the transition. Results here have shown that the transition point is located at a temperature beyond 300°C.